A yttrium-doped iridium oxide catalyst, a preparation method and application thereof
Patent Information
- Application Number
- CN202410369600.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-28
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-03-28
AI Technical Summary
当前全球的主流制氢工艺是以煤和天然气等化石燃料重整的“灰氢”制备,能够提供全球70-80%的氢能需求,其制备过程中的碳排放量大且制备的氢气纯度较低
[0025]1、本发明提出了一种钇掺杂氧化铱催化剂,通过一步熔盐法即可将稀土元素钇均匀掺杂至氧化铱中;相较于传统合成方法,本发明的制备方法简单,易于批量大规模生产,所得片状催化剂具有较大的电化学活性面积,有助于提升催化性能;
Smart Images

Figure CN118371243B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nanocatalyst technology, specifically relating to a yttrium-doped iridium oxide catalyst, its preparation method, and its application. Background Technology
[0002] Hydrogen energy, as a diverse, clean, and low-carbon secondary energy source, is rapidly expanding its applications in transportation, energy storage, power generation, and industry. It also boasts advantages such as high energy density and simple storage methods, making it an ideal choice for large-scale, long-term energy storage. Currently, the mainstream global hydrogen production process uses "gray hydrogen" produced from reforming fossil fuels like coal and natural gas, capable of providing 70-80% of global hydrogen demand. However, this process generates significant carbon emissions and produces hydrogen with relatively low purity. The production of "blue hydrogen," a second type of hydrogen, while capturing, storing, and utilizing released CO2, still relies on fossil fuels, contradicting the global energy transition trend. "Green hydrogen," a third type of hydrogen, is produced using water electrolysis coupled with renewable energy sources such as wind and solar power. This process produces hydrogen with no carbon emissions, high purity, and high energy conversion efficiency, without dependence on traditional fossil fuels, making it considered the most ideal hydrogen production route. However, the extremely acidic environment of PEM (proton exchange membrane) anodes places high demands on catalysts, and most anode oxygen evolution catalysts exhibit poor acid resistance and stability. So far, iridium-based oxides (IrO) x It is the only known oxygen evolution catalyst that can be industrially applied on a large scale in PEM.
[0003] Current IrO x The catalysts still suffer from high cost and poor durability, making it difficult to meet the requirements of high performance and long-term stability at commercial current densities (1.5 A current density at 80°C). Therefore, designing and preparing highly active and durable water electrolysis catalysts is key to the widespread application of this technology. Recent studies have shown that iridium oxide, doped with different elements, exhibits high activity in acidic oxygen evolution reactions (PEMWEs). This can increase the binding energy of iridium sites to key oxygen-containing intermediates, thereby improving the intrinsic activity of the catalyst and enhancing its stability in acidic media. This has important guiding significance for developing efficient oxygen evolution catalysts for PEMWE applications. Summary of the Invention
[0004] Regarding the IrO in the aforementioned prior art x To address the existing problems with catalysts, this invention provides a yttrium-doped iridium oxide catalyst, its preparation method, and its application. This catalyst helps improve the activity and stability of oxygen evolution during water electrolysis in acidic electrolytes, is suitable for large-scale batch production, and can meet the requirements of high performance and long-term stability at commercial current densities.
[0005] To achieve the above objectives, the technical method employed in this invention is as follows:
[0006] A yttrium-doped iridium oxide catalyst is formed by uniformly doping rare earth element yttrium into iridium oxide through a one-step molten salt method to form a sheet-like catalyst; wherein the molar ratio of yttrium to iridium is 1:(5-20).
[0007] Furthermore, the size of the sheet-like catalyst is on the micrometer scale.
[0008] A method for preparing a yttrium-doped iridium oxide catalyst includes the following steps:
[0009] Step 1: Put potassium nitrate and / or sodium nitrate into a muffle furnace and heat until melted to obtain molten salt;
[0010] Step 2: After mixing and grinding the iridium-based compound and the yttrium-based compound, add them to the molten salt that has not been cooled, so that the mixture of the iridium-based compound and the yttrium-based compound is covered by the molten salt, and put it into the muffle furnace again for heat treatment to obtain the precursor; wherein, the molar ratio of iridium atoms in the iridium-based compound to yttrium atoms in the yttrium-based compound is 1:(5~20);
[0011] Step 3: After the precursor is removed and cooled to room temperature, it is poured into deionized water and sonicated. The resulting mixture is then subjected to multiple centrifugations and ultrasonic washings, followed by vacuum drying to obtain the yttrium-doped iridium oxide catalyst.
[0012] Furthermore, in step 1, the mass ratio of potassium nitrate to sodium nitrate is 1:(1-3).
[0013] Furthermore, the iridium-based compound is iridium chloride or iridium acetate, etc.
[0014] Furthermore, the yttrium-based compound is yttrium chloride or yttrium nitrate, etc.
[0015] Furthermore, the temperature for the heating process in step 1 is 360–400 degrees Celsius, and the temperature is maintained for 30–60 minutes.
[0016] Furthermore, the heating rate in step 1 is 5–10 degrees Celsius per minute.
[0017] Furthermore, the temperature of the heat preservation treatment in step 2 is the same as the temperature of the heating treatment in step 1, and the heat preservation time is 60 to 120 minutes.
[0018] Furthermore, the duration of ultrasound in step 3 is 120–200 minutes.
[0019] Furthermore, the specific process of centrifugation and ultrasonic washing in step 3 is as follows: first, centrifuge the obtained mixture, collect the product and ultrasonically wash it with deionized water or a polar solvent; then continue centrifugation, collect the product and ultrasonically wash it with deionized water or a polar solvent; repeat the process of centrifugation and ultrasonic washing 3 to 5 times.
[0020] Furthermore, the centrifugation speed is 10,000 to 12,000 revolutions per minute, the centrifugation time is 5 to 8 minutes, and the ultrasonic washing time is 5 to 10 minutes.
[0021] Furthermore, the polar solvent includes, but is not limited to, anhydrous ethanol and isopropanol.
[0022] Furthermore, in step 3, the vacuum drying temperature is 50–80 degrees Celsius, and the drying time is 10–24 hours.
[0023] The present invention also provides the application of the yttrium-doped iridium oxide catalyst described in any of the above technical solutions or the yttrium-doped iridium oxide catalyst prepared by any of the above technical solutions in the acidic oxygen evolution reaction of water electrolysis to produce hydrogen.
[0024] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0025] 1. This invention proposes a yttrium-doped iridium oxide catalyst, in which rare earth element yttrium can be uniformly doped into iridium oxide through a one-step molten salt method. Compared with traditional synthesis methods, the preparation method of this invention is simple, easy to mass-produce, and the resulting sheet-like catalyst has a large electrochemical active area, which helps to improve catalytic performance.
[0026] 2. The yttrium-doped iridium oxide catalyst provided by this invention, when applied to the three-electrode system of a traditional H-type electrolyzer, achieves an overpotential of only 170 mV at a current density of 10 mA and maintains stable oxygen evolution performance for more than 100 hours at a high current density of 100 mA. When applied to a commercial proton exchange membrane electrolyzer, it achieves stable hydrogen production for more than 100 hours at a current density of 1.5 A at 80 degrees Celsius, meeting the requirements of high performance and long-term stability at commercial current densities. Attached Figure Description
[0027] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0028] Figure 1This is a transmission electron microscope image of the yttrium-doped iridium oxide catalyst obtained in Example 1 of the present invention;
[0029] Figure 2 The X-ray diffraction pattern of the yttrium-doped iridium oxide catalyst obtained in Example 1 of this invention is shown below.
[0030] Figure 3 The X-ray photoelectron spectrum of the yttrium-doped iridium oxide catalyst obtained in Example 1 of this invention is shown below; where (a) represents Ir 4f and (b) represents Y 3d.
[0031] Figure 4 The polarization curves of the yttrium-doped iridium oxide catalyst and the undoped iridium oxide catalyst obtained in Example 1 of the present invention under acidic oxygen evolution reaction in an H-type electrolytic cell;
[0032] Figure 5 This is a comparison of the polarization curves of the yttrium-doped iridium oxide catalyst and the undoped iridium oxide catalyst obtained in Example 1 of the present invention, with the electrochemical active area normalized in an H-type electrolytic cell.
[0033] Figure 6 The potential change curve of the yttrium-doped iridium oxide catalyst obtained in Example 1 of the present invention over time at a current density of 10 mA per square centimeter in an H-type electrolytic cell;
[0034] Figure 7 The potential change curve of the yttrium-doped iridium oxide catalyst obtained in Example 1 of the present invention over time at a current density of 100 mA per square centimeter in an H-type electrolytic cell;
[0035] Figure 8 The potential change curve of the yttrium-doped iridium oxide catalyst obtained in Example 1 of the present invention in a proton exchange membrane electrolyzer at 80 degrees Celsius and a current density of 1.5 A / cm² over time. Detailed Implementation
[0036] To further understand the present invention, preferred embodiments are described below with reference to examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, and not for limiting the scope of the claims. All raw materials used in the present invention are not particularly limited in their source; they can be purchased commercially or prepared using conventional methods well known to those skilled in the art.
[0037] Example 1
[0038] This embodiment prepares a yttrium-doped iridium oxide catalyst, specifically including the following steps:
[0039] Step 1: Take 5g of potassium nitrate and 5g of sodium nitrate, mix and grind them, place them in a crucible, and then put them in a muffle furnace. Heat the crucible to 380 degrees Celsius at a heating rate of 5 degrees Celsius per minute, and hold for 30 minutes to obtain molten salt.
[0040] Step 2: Weigh 58.6 mg of iridium chloride, add iridium chloride and yttrium nitrate into a dry mortar, and grind for 20 minutes until fully mixed to obtain a mixed powder; wherein, the molar ratio of iridium atoms in iridium chloride to yttrium atoms in yttrium nitrate is 9:1;
[0041] Step 3: Take out the molten salt obtained in Step 1 and immediately add the mixed powder obtained in Step 2 into it. Stir slightly to cover the mixed powder with molten salt, and continue to put it into the muffle furnace for heat treatment. The heat treatment temperature is 380 degrees Celsius and the heat treatment time is 60 minutes to obtain the precursor.
[0042] Step 4: Remove the crucible containing the precursor and cool it to room temperature. Add deionized water and sonicate for 180 minutes to obtain a mixed solution. Add 5 mL of anhydrous ethanol to the mixed solution, centrifuge, collect the product, and sonicate it with deionized water. Then add another 5 mL of anhydrous ethanol and centrifuge again. Collect the product and sonicate it with anhydrous ethanol. Repeat the centrifugation and sonication process three times. Collect the product and place it in a vacuum drying oven. Dry it at 60 degrees Celsius for 12 hours. Grind it to obtain the yttrium-doped iridium oxide catalyst. The centrifugation speed was 12,000 rpm, the centrifugation time was 5 minutes, and the sonication time was 10 minutes.
[0043] Figure 1 The image shown is a transmission electron microscope image of the yttrium-doped iridium oxide catalyst obtained in this embodiment. It can be seen that the obtained yttrium-doped iridium oxide catalyst is in the form of micron-sized sheets, which theoretically has a large electrochemical active area.
[0044] Figure 2 The X-ray diffraction pattern of the yttrium-doped iridium oxide catalyst obtained in this embodiment corresponds to the PDF standard card of IrO2. At the same time, no peaks of Y-based oxides are seen, indicating that the doping effect is good and no segregation phenomenon occurs.
[0045] Figure 3 The image shows the X-ray photoelectron spectrum of the yttrium-doped iridium oxide catalyst obtained in this embodiment. Figure 3 (a) is Ir 4f, Figure 3 (b) is Y 3d, which shows that compared with pure iridium oxide, the electronic structure of the iridium surface of the obtained yttrium-doped iridium oxide catalyst is regulated, indicating that the rare earth element yttrium is doped into iridium oxide.
[0046] Comparative Example
[0047] This comparative example prepared an undoped iridium oxide catalyst. The preparation process was the same as that in Example 1, except that yttrium nitrate was not added in step 2.
[0048] The oxygen evolution performance of the yttrium-doped iridium oxide catalyst obtained in Example 1 and the undoped iridium oxide catalyst obtained in the comparative example were tested in an H-type electrolyzer. Specifically:
[0049] In the H-type electrolytic cell, carbon paper loaded with a catalyst is used as the anode, a mercury / mercurous sulfate electrode in a saturated potassium sulfate solution is used as the reference electrode, and the cathode reaction is the hydrogen evolution reaction of the carbon rod.
[0050] Using dilute sulfuric acid with a concentration of 0.5 mol / L as the electrolyte, carbon paper with an area of 1 square centimeter loaded with the yttrium-doped iridium oxide catalyst obtained in Example 1 and carbon paper loaded with the undoped iridium oxide catalyst obtained in the comparative example were immersed in the electrolyte for polarization performance testing.
[0051] The results of the polarization performance test are as follows Figure 4 As shown, the yttrium-doped iridium oxide catalyst obtained in Example 1 reaches a current density of 10 mA at an overpotential of 170 mV, demonstrating a significant improvement in activity compared to the undoped iridium oxide catalyst. Simultaneously, the intrinsic activity of the yttrium-doped iridium oxide catalyst obtained in Example 1 and the undoped iridium oxide catalyst obtained in the comparative example were tested using the double-layer capacitance method, and the normalized performance of the electrochemical active area was tested. The test results are as follows. Figure 5 As shown, the intrinsic activity of the iridium oxide catalyst is better after being doped with the rare earth element yttrium.
[0052] Using 0.5 mol / L dilute sulfuric acid as the electrolyte, a load with an area of 1 square centimeter was prepared.
[0053] The carbon paper containing the yttrium-doped iridium oxide catalyst obtained in Example 1 was immersed in an electrolyte, and its stability was tested using a constant current method. The potential change curves over time at current densities of 10 mA / cm² and 100 mA / cm² are shown below. Figure 6 and Figure 7 As shown, it can be seen that the yttrium-doped iridium oxide catalyst obtained in Example 1 can operate stably for more than 100 hours at current densities of 10 mA / cm² and 100 mA / cm², demonstrating the excellent activity and stability of the catalyst.
[0054] The water electrolysis performance of the yttrium-doped iridium oxide catalyst obtained in Example 1 was tested in a PEM electrolyzer, specifically as follows:
[0055] The PEM electrolyzer uses a proton exchange membrane 117, with the cathode catalyst and anode catalyst coated on both sides of the membrane to form a membrane electrode. Ti felt is used as a gas diffusion layer and a current collector on both sides of the membrane electrode. The cathode catalyst is a commercial platinum carbon (platinum: 20%), and the anode catalyst is the yttrium-doped iridium oxide catalyst obtained in Example 1.
[0056] The specific preparation method of the membrane electrode is as follows: 5 mg of the yttrium-doped iridium oxide catalyst obtained in Example 1 was dissolved in a mixture of 1 mL isopropanol and 50 μL perfluorosulfonic acid 117 dispersion (Nafion), and ultrasonicated in an ice bath for 30 minutes to form an anode catalyst slurry; 5 mg of commercial platinum-carbon catalyst was dissolved in a mixture of 1 mL isopropanol and 50 μL Nafion, and ultrasonicated in an ice bath for 30 minutes to form a cathode catalyst slurry; the cathode catalyst slurry and the anode catalyst slurry were uniformly sprayed onto both sides of the proton exchange membrane using a spray gun, with a sprayed geometric area of 2*2 cm. During the catalyst slurry spraying process, the proton exchange membrane is adsorbed onto the platform through a vacuum heating stage to keep the membrane flat. The heating stage temperature is 80 degrees Celsius. The spraying order of the cathode catalyst slurry and the anode catalyst slurry has no substantial impact on the performance characterization of the membrane electrode. After spraying, the membrane electrode loaded with the cathode catalyst and the anode catalyst is hot-pressed using a hot press to improve the adhesion between the catalyst and the proton exchange membrane. The hot-pressing temperature is 100 degrees Celsius, the hot press pressure is set to 2 MPa, and the hot-pressing time is 3 minutes. After hot pressing, the membrane electrode is assembled with the PEM electrolyzer.
[0057] The assembled PEM electrolyzer was connected to the electrochemical workstation, auxiliary circulating water system, and heating device. Deionized water was used as the reactant, the water circulation rate was 2.5 ml / min, and the reaction temperature was 80 degrees Celsius. Stability testing was conducted using a constant current method, and the test results are as follows: Figure 8 As shown, the yttrium-doped iridium oxide catalyst obtained in Example 1 can operate stably for more than 100 hours at a current density of 1.5 A / cm², meeting the requirements for high performance and long-term stability at commercial current densities.
[0058] Example 2
[0059] This embodiment prepares a yttrium-doped iridium oxide catalyst, specifically including the following steps:
[0060] Step 1: Mix and grind 5g of potassium nitrate and 15g of sodium nitrate, place them in a crucible, and then put them in a muffle furnace. Heat the crucible to 380 degrees Celsius at a heating rate of 5 degrees Celsius per minute and hold for 60 minutes to obtain molten salt.
[0061] Step 2: Weigh 58.6 mg of iridium chloride, add iridium chloride and yttrium nitrate into a dry mortar, and grind for 20 minutes until fully mixed to obtain a mixed powder; wherein, the molar ratio of iridium atoms in iridium chloride to yttrium atoms in yttrium nitrate is 9:1;
[0062] Step 3: Take out the molten salt obtained in Step 1 and immediately add the mixed powder obtained in Step 2 into it. Stir slightly to cover the mixed powder with molten salt, and continue to put it into the muffle furnace for heat treatment. The heat treatment temperature is 380 degrees Celsius and the heat treatment time is 120 minutes to obtain the precursor.
[0063] Step 4: Remove the crucible containing the precursor and cool it to room temperature. Add deionized water and sonicate for 180 minutes to obtain a mixed solution. Add 5 mL of anhydrous ethanol to the mixed solution, centrifuge, collect the product, and sonicate it with deionized water. Then add another 5 mL of anhydrous ethanol and centrifuge again. Collect the product and sonicate it with anhydrous ethanol. Repeat the centrifugation and sonication process three times. Collect the product and place it in a vacuum drying oven. Dry it at 60 degrees Celsius for 12 hours. Grind it to obtain the yttrium-doped iridium oxide catalyst. The centrifugation speed was 12,000 rpm, the centrifugation time was 5 minutes, and the sonication time was 10 minutes.
[0064] Example 3
[0065] This embodiment prepares a yttrium-doped iridium oxide catalyst, specifically including the following steps:
[0066] Step 1: Take 5g of potassium nitrate, grind it, place it in a crucible, and then put it in a muffle furnace. Heat it to 380 degrees Celsius at a heating rate of 5 degrees Celsius per minute, and hold it for 30 minutes to obtain molten salt.
[0067] Step 2: Weigh 58.6 mg of iridium chloride, add iridium chloride and yttrium nitrate into a dry mortar, and grind for 20 minutes until fully mixed to obtain a mixed powder; wherein, the molar ratio of iridium atoms in iridium chloride to yttrium atoms in yttrium nitrate is 19:1;
[0068] Step 3: Take out the molten salt obtained in Step 1 and immediately add the mixed powder obtained in Step 2 into it. Stir slightly to cover the mixed powder with molten salt, and continue to put it into the muffle furnace for heat treatment. The heat treatment temperature is 380 degrees Celsius and the heat treatment time is 30 minutes to obtain the precursor.
[0069] Step 4: Remove the crucible containing the precursor and cool it to room temperature. Add deionized water and sonicate for 180 minutes to obtain a mixed solution. Add 5 mL of anhydrous ethanol to the mixed solution, centrifuge, collect the product, and sonicate it with deionized water. Then add another 5 mL of anhydrous ethanol and centrifuge again. Collect the product and sonicate it with anhydrous ethanol. Repeat the centrifugation and sonication process three times. Collect the product and place it in a vacuum drying oven. Dry it at 60 degrees Celsius for 12 hours. Grind it to obtain the yttrium-doped iridium oxide catalyst. The centrifugation speed was 12,000 rpm, the centrifugation time was 5 minutes, and the sonication time was 10 minutes.
[0070] Example 4
[0071] This embodiment prepares a yttrium-doped iridium oxide catalyst, specifically including the following steps:
[0072] Step 1: Take 5g of sodium nitrate, mix and grind it, place it in a crucible, and then put it in a muffle furnace. Heat it to 400 degrees Celsius at a heating rate of 5 degrees Celsius per minute, and hold it for 30 minutes to obtain molten salt.
[0073] Step 2: Weigh 58.6 mg of iridium chloride, add iridium chloride and yttrium nitrate into a dry mortar, and grind for 20 minutes until fully mixed to obtain a mixed powder; wherein, the molar ratio of iridium atoms in iridium chloride to yttrium atoms in yttrium nitrate is 5:1;
[0074] Step 3: Take out the molten salt obtained in Step 1 and immediately add the mixed powder obtained in Step 2 into it. Stir slightly to cover the mixed powder with molten salt, and continue to put it into the muffle furnace for heat treatment at 400 degrees Celsius for 60 minutes to obtain the precursor.
[0075] Step 4: Remove the crucible containing the precursor and cool it to room temperature. Add deionized water and sonicate for 180 minutes to obtain a mixed solution. Add 5 mL of anhydrous ethanol to the mixed solution, centrifuge, collect the product, and sonicate it with deionized water. Then add another 5 mL of anhydrous ethanol and centrifuge again. Collect the product and sonicate it with anhydrous ethanol. Repeat the centrifugation and sonication process three times. Collect the product and place it in a vacuum drying oven. Dry it at 60 degrees Celsius for 12 hours. Grind it to obtain the yttrium-doped iridium oxide catalyst. The centrifugation speed was 12,000 rpm, the centrifugation time was 5 minutes, and the sonication time was 10 minutes.
[0076] Specific examples have been used to illustrate the principles and implementation methods of this invention. The descriptions of these embodiments are merely to aid in understanding the method and core ideas of this invention, including the best mode, and to enable any person skilled in the art to practice this invention, including manufacturing and using any device or system, and implementing any combined method. It should be noted that those skilled in the art can make various improvements and modifications to this invention without departing from its principles, and these improvements and modifications also fall within the scope of protection of the claims. The scope of protection of this patent is defined by the claims and may include other embodiments that can be conceived by those skilled in the art. If these other embodiments have structural elements that are not different from the wording of the claims, or if they include equivalent structural elements that are not substantially different from the wording of the claims, then these other embodiments should also be included within the scope of the claims.
Claims
1. A yttrium-doped iridium oxide catalyst, characterized in that, The rare earth element yttrium is uniformly doped into iridium oxide using a one-step molten salt method to form a micron-sized sheet-like catalyst. The preparation method specifically includes the following steps: Step 1: Put potassium nitrate and / or sodium nitrate into a muffle furnace and heat until melted to obtain molten salt; Step 2: After mixing and grinding the iridium-based compound and the yttrium-based compound, add them to the molten salt that has not been cooled down, so that the mixture of the iridium-based compound and the yttrium-based compound is covered by the molten salt. Then put it into the muffle furnace again for heat treatment to obtain the precursor. Step 3: After the precursor is removed and cooled to room temperature, it is poured into deionized water and sonicated. The resulting mixture is then subjected to multiple centrifugations and ultrasonic washings, followed by vacuum drying to obtain the yttrium-doped iridium oxide catalyst. The molar ratio of yttrium to iridium is 1:(5~20).
2. The yttrium-doped iridium oxide catalyst according to claim 1, characterized in that, In step 1, the mass ratio of potassium nitrate to sodium nitrate is 1:(1~3).
3. The yttrium-doped iridium oxide catalyst according to claim 1, characterized in that, The iridium-based compound is iridium chloride or iridium acetate.
4. The yttrium-doped iridium oxide catalyst according to claim 1, characterized in that, The yttrium-based compound is yttrium chloride or yttrium nitrate.
5. The yttrium-doped iridium oxide catalyst according to claim 1, characterized in that, In step 1, the temperature for heating is 360-400 degrees Celsius, and the temperature is maintained for 30-60 minutes.
6. The yttrium-doped iridium oxide catalyst according to claim 5, characterized in that, The temperature of the heat preservation treatment in step 2 is the same as the temperature of the heating treatment in step 1, and the heat preservation time is 60~120 minutes.
7. The yttrium-doped iridium oxide catalyst according to claim 1, characterized in that, The heating rate in step 1 is 5-10 degrees Celsius per minute.
8. The application of the yttrium-doped iridium oxide catalyst according to any one of claims 1 to 7 in the acidic oxygen evolution reaction of water electrolysis to produce hydrogen.